(3JMaI GdRef aj SGOGJ Gdjefs - (3GdMSjf Hf YHO GdQMef Hf eMeO Hf Ydj Hf CHj HcQ Hf Ydj GdGgOd, HOQ GdOjf GdGgOd,J (B855 (3g` s
(3ChdgG (B:s
(3GeG HYO aEf Yde GdJhGQjN ef GdYdhe GdeajOI EP Hg jMUd ddNda Yde CMhGd GdSda s
(3BNQgG (B:s
(3afRdJ Ydjge hQbI NVQkG ef GdSeGA ecJhH HGdfhQ HQGAI ef Gddg dYdi hYeQ s
(3Hg ChQGb ai BNQg HjVGA GfJNHg ef JGQjN Gdjef ddHOQ GdLfOi ai BNQg JeRb TOjOs
(3JHUQGJ GdCUd (B:s
(3HgG NQe s
(3MGdI GdfSNI eJhSWI s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3eJaQbGJs